2020
DOI: 10.1007/s12325-020-01277-2
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Dose Combination of Netarsudil and Latanoprost in Ocular Hypertension and Open-Angle Glaucoma: Pooled Efficacy/Safety Analysis of Phase 3 MERCURY-1 and -2

Abstract: Introduction: New open-angle glaucoma (OAG) and ocular hypertension (OHT) therapies that reduce treatment burden and improve outcomes relative to currently available agents are needed. Netarsudil, a novel Rho kinase inhibitor approved by the US Food and Drug Administration, reduces intraocular pressure (IOP) by increasing trabecular outflow. Two phase 3 superiority studies compared a fixeddose combination (FDC) of netarsudil and the prostaglandin latanoprost with each active component for IOP-lowering efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 18 publications
3
52
0
Order By: Relevance
“…Although approximately onethird of subjects experienced treatment-related adverse events (most commonly, conjunctival hyperemia), none of these were serious adverse events, and only 11% of subjects discontinued the study due to adverse events. The discontinuation rate is comparable to the 3-month netarsudil dropout rates from the pooled ROCKET monotherapy trials (66/ 494 subjects [13.4%]) and the pooled monotherapy arms of the MERCURY-1 and 2 trials (70/499 subjects [14.0%]) 29,30 . Hyperemia was generally mild and sporadic, with only 1 case of severe hyperemia.…”
Section: Discussionmentioning
confidence: 61%
“…Although approximately onethird of subjects experienced treatment-related adverse events (most commonly, conjunctival hyperemia), none of these were serious adverse events, and only 11% of subjects discontinued the study due to adverse events. The discontinuation rate is comparable to the 3-month netarsudil dropout rates from the pooled ROCKET monotherapy trials (66/ 494 subjects [13.4%]) and the pooled monotherapy arms of the MERCURY-1 and 2 trials (70/499 subjects [14.0%]) 29,30 . Hyperemia was generally mild and sporadic, with only 1 case of severe hyperemia.…”
Section: Discussionmentioning
confidence: 61%
“… 21 The most common adverse event was conjunctival hyperemia (63%), followed by instillation site pain (23%), conjunctival hemorrhage (13%), and cornea verticillata (17.6%). 21 …”
Section: Rock Inhibitors and Their Role In Glaucomamentioning
confidence: 99%
“…PG324: In 2019, Aerie Pharmaceuticals also introduced PG324 (Rocklatan ® ), an FDA approved fixed-dose combination of Netarsudil (0.02%) and latanoprost (0.005%). 21 Two Phase 3 studies (MERCURY 1 and MERCURY 2) showed that this combination significantly lowered IOP and was superior to both Netarsudil and latanoprost alone. 21 The most common adverse event was conjunctival hyperemia (63%), followed by instillation site pain (23%), conjunctival hemorrhage (13%), and cornea verticillata (17.6%).…”
Section: Rock Inhibitors and Their Role In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Both of the triple FDC showed no serious adverse events and they were reported to be as safe as and well tolerated as bimatoprost/timolol FC and dorzolamide/timolol FC [66]. Soon after the development of netarsudil, Aerie Pharmaceuticals Inc (Durham, NC, USA) developed an FDC combining netarsudil and latanoprost and has recently been tested in two Phase III clinical trials, MERCURY-1 and MERCURY-2 [70]- [72]. The most commonly reported adverse event was conjunctival hyperaemia and the FDC otherwise has negligible treatment-related serious local or systemic adverse drug reactions.…”
Section: Combination Treatmentmentioning
confidence: 99%